2020
DOI: 10.1002/art.41215
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Weakness in Myositis: MicroRNA‐Mediated Dystrophin Reduction in a Myositis Mouse Model and Human Muscle Biopsies

Abstract: Objective Muscle inflammation is a feature in myositis and Duchenne muscular dystrophy ( DMD ). Autoimmune mechanisms are thought to contribute to muscle weakness in patients with myositis. However, a lack of correlation between the extent of inflammatory cell infiltration and muscle weakness indicates that nonimmune pathologic mechanisms may play a role. The present study focused on 2 micro RNA (mi RNA ) sets previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Serum miR-146b is a pharmacodynamic biomarker in inflammatory bowel disease (IBD) [ 34 , 35 ]. Intriguingly, miR-146b is also known to down-regulate dystrophin in multiple muscle diseases, is increased in dystrophinopathies and in myositis, and is also drug-responsive in the mdx mouse model of DMD [ 30 , 31 ]. Urinary miR-141 provides a promising diagnostic biomarker for the identification of both prostate and bladder cancers [ 69 ]; it will be interesting to determine if this or other candidate miRNAs are also dysregulated in urine from dystrophic patients, as this sampling method could provide a completely non-invasive biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum miR-146b is a pharmacodynamic biomarker in inflammatory bowel disease (IBD) [ 34 , 35 ]. Intriguingly, miR-146b is also known to down-regulate dystrophin in multiple muscle diseases, is increased in dystrophinopathies and in myositis, and is also drug-responsive in the mdx mouse model of DMD [ 30 , 31 ]. Urinary miR-141 provides a promising diagnostic biomarker for the identification of both prostate and bladder cancers [ 69 ]; it will be interesting to determine if this or other candidate miRNAs are also dysregulated in urine from dystrophic patients, as this sampling method could provide a completely non-invasive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…In Duchenne and Becker muscular dystrophies, myomiRs are up-regulated in serum from both patient populations, while detection of miR-206 up-regulation can be used to differentially diagnose severe Duchenne versus Becker patients [ 26 , 27 , 28 ]. In addition to myomiRs, inflammatory miRNAs such as miR-146a, miR-146b, miR-221 and miR-155 have been found to be dysregulated in multiple forms of muscular dystrophies [ 29 , 30 , 31 ]. These two classes of miRNA show potential as pharmacodynamic biomarkers, with myomiRs proposed for muscle-stabilizing treatments such as gene therapy [ 32 , 33 ], and inflammatory microRNAs proposed for current steroids [ 34 , 35 ] as well as newly emerging dissociative anti-inflammatory drugs such as vamorolone [ 36 , 37 , 38 ] or edasalonexent [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR‐455‐5p has been shown to play an anti‐inflammatory role in the immune system 26 . Recent studies have shown that miR‐455‐5p is significantly elevated in mice with severe myositis (~4–6‐fold increase; p < .05), 12 suggesting that miR‐455‐5p may be involved in muscle development. In this study, we showed for the first time that miR‐455‐5p is involved in monitoring myotube morphogenesis in addition to its established roles in cancer and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, miR‐455‐5p is located on chromosome 4 and is encoded by Col27a1 (collagen type XXVII alpha 1 chain). Mice with severe myositis show elevated expression of miR‐455‐5p 13 . TTTY15/miR‐455‐5p/JDP2 axis regulates hypoxia‐induced cell injuries in human cardiomyocyte primary cells 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Patient muscles exhibiting refractory weakness without inflammatory cell infiltration have been observed to have chronic MHC class I over-expression, even after prednisone treatment (Lundberg et al, 2000; Nyberg et al, 2000). Additionally, transgenic over-expression of MHC class I in mouse skeletal muscle recapitulates many features of myositis, including endoplasmic reticulum (ER) stress and up-regulation of ISGs (Kinder et al, 2020; Nagaraju et al, 2000). Taken together, chronic expression of MHC class I, or certain alleles of it, may be pathogenic in skeletal muscle and could be a therapeutic target in myositis ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%